Computational Analysis of Tinospora Cordifolia Phytochemicals as Potential Inhibitors of BRCA1-BRCT Domain Interaction in Breast Cancer - Vaishnavi Rajendra Bendkhale (International Journal of Molecular Biotechnological Research, 2025)
Breast cancer is a leading cause of cancer-related deaths worldwide, accounting for a significant proportion of mortality rates among women. Despite current therapeutic approaches, the disease remains characterized by molecular heterogeneity, making it challenging to develop effective treatments. This study explores the potential of Tinospora cordifolia, a medicinal plant, in breast cancer therapy. Guduchi, scientifically known as Tinospora cordifolia, boasts a centuries-long history of use in traditional medicine, with a substantial body of research investigating its anti-cancer properties. Using a computational approach, several phytocompounds with potential anti-cancer properties were identified from Tinospora cordifolia. These compounds exhibited favorable pharmacological properties, including lipophilicity, solubility, and bioavailability, making them suitable for further development. Moreover, molecular docking studies revealed that these compounds had high binding affinity to the BRCT protein, a critical component of the BRCA1 gene. Mutations in the BRCA1 gene, which is vital for DNA repair, have been linked to a heightened risk of developing breast cancer. The identification of Tinospora cordifolia-derived phytocompounds with potential anti-cancer properties is a significant finding, offering a promising avenue for the development of novel cancer treatments. The potential of these compounds as therapeutic agents is promising, making them suitable lead molecules for further research and development. This study demonstrates the potential of Tinospora cordifolia in breast cancer therapy and highlights the importance of exploring traditional medicinal plants as a source of novel anti-cancer agents. Additional research is necessary to uncover the full therapeutic potential of these compounds and to translate this knowledge into effective breast cancer treatments.
Keywords: BRCA1; BRCA2; Guduchi; Medicinal Plants; Pharmacological Studies; T. cordifolia; breast cancer; cancer treatment; drug development; herbal medicine; molecular docking; oncology